STUDY OF VERTICAL DISTANCE BETWEEN SUPRAORBITAL FORAMEN AND INFRAORBITAL FORAMEN AMONG NORTH INDIAN HUMAN DRY SKULLS - GUPTA, SUBHASH; NIRALA, KAMTA PRASAD; SHUKLA, MISS SAGUN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The aim of study was to document the positional distance of supraorbital foramen (SOF) in relation to Infraorbital foramen (IOF), which is necessary for periorbital procedures. Materials and Methods: A total of 72 dry human skulls of unknown age and gender from North India, were studied. In each skull, distance between supraorbital and IOF was measured on both sides using a metal casing Vernier Caliper. Results: The mean distance between inferior wall of SOF and superior wall of IOF was found to be 40.81 (±6.66) mm on the left side and 40.91 (±6.15) mm on the right side. The overall value for both sides was 40.86 (±6.28) mm Conclusion: Precise knowledge about distance between supraorbital and IOF have important bearings on orbital and periorbital procedures. It provides guidance for anesthesiologists and facial surgeons